2007
DOI: 10.1002/cphc.200600491
|View full text |Cite
|
Sign up to set email alerts
|

Direct Coupling of Bromine‐Mediated Methane Activation and Carbon‐Deposit Gasification

Abstract: The direct bromination of methane offers a quite selective (>98 %) route towards methane activation but shifts the problem of fuel production to converting and handling corrosive methyl bromide. The direct conversion of methyl bromide, at about 200 degrees C, into light hydrocarbons can be catalyzed under pressure by AlBr(3) resulting in the formation of propane-rich mixtures of light hydrocarbons, carbonaceous deposits, and HBr. After releasing the gaseous products, the addition of hydrogen at 260 degrees C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 65 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…Indeed, it has been demonstrated that polyhalogenated alkanes are a major precursor to heavier hydrocarbons, such as long‐chain alkanes and aromatics, and ultimately result in significant coking of the catalyst 48. Attempts to isolate monohaloalkanes at high selectivity have so far involved the development of non‐radical‐based catalytic systems,45, 49, 50 to avoid the expected homogeneous free‐radical chain reactions51—and the utilisation of Br 2 as opposed to Cl 2 as halogen source; the weaker CBr bond results in a more controlled halogenation pathway and typically higher monohalogenated selectivities, albeit at the expense of conversion 52. The utilisation of Br 2 also presents an additional advantage, given that the so‐formed monohalogenated liquid product is significantly easier to handle than the gaseous Cl 2 analogue.…”
Section: Oxidation Of Methane To Olefinsmentioning
confidence: 99%
“…Indeed, it has been demonstrated that polyhalogenated alkanes are a major precursor to heavier hydrocarbons, such as long‐chain alkanes and aromatics, and ultimately result in significant coking of the catalyst 48. Attempts to isolate monohaloalkanes at high selectivity have so far involved the development of non‐radical‐based catalytic systems,45, 49, 50 to avoid the expected homogeneous free‐radical chain reactions51—and the utilisation of Br 2 as opposed to Cl 2 as halogen source; the weaker CBr bond results in a more controlled halogenation pathway and typically higher monohalogenated selectivities, albeit at the expense of conversion 52. The utilisation of Br 2 also presents an additional advantage, given that the so‐formed monohalogenated liquid product is significantly easier to handle than the gaseous Cl 2 analogue.…”
Section: Oxidation Of Methane To Olefinsmentioning
confidence: 99%
“…The oxidative bromination of alkanes as an alternative approach for light alkane conversion was investigated in recent years [1][2][3][4][5][6][7][8][9][10][11][12]. In Schweizer et al's patent [13], a process was described to halogenate CH 4 to CH 3 X (X is halogen), and then convert CH 3 X to higher hydrocarbons or acetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic compounds such as benzene, toluene, xylene and trimethylbenzene are important raw materials in the chemical industry; they are collected as by-products of coal coking or derived from processes of catalytic reforming and gasoline cracking. There are various routes for the conversion of natural gas into aromatic hydrocarbons, e.g., the direct aromatization route [2][3][4], syngas route [5][6][7], chloride route [8][9][10][11][12], and bromide route [13][14][15]. Recently, we reported a new route: first CH 3 Br is formed from CH 4 using HBr/H 2 O as mediator in the presence of oxygen, and then CH 3 Br is catalytically transformed into hydrocarbons or compounds of high carbon number [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%